2008
DOI: 10.1158/1078-0432.ccr-08-0706
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Screening Identifies Cardiac Glycosides as Potent Inhibitors of Human Tissue Kallikrein Expression: Implications for Cancer Therapies

Abstract: Purpose: Human tissue kallikreins (KLK) comprise a subgroup of 15 homologous secreted serine proteases. Primarily known for their clinical use as cancer biomarkers (e.g., PSA), KLKs have recently been directly implicated in cancer-related processes, including invasion, angiogenesis, and tumor growth regulation. Therefore, the identification of compounds that would modulate expression of KLKs might be of considerable therapeutic value. Experimental Design: A cell-based high-throughput screening (HTS) of three s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 37 publications
2
13
0
Order By: Relevance
“…The other HTS hit compounds already in ongoing clinical trials 5 in prostate cancer included doxorubicin, Taxol/paclitaxel, mitoxantrone, suramin, camptothecin, staurosporine, ixabepilone, 17-AAG, epothilone B, MS-275, and vinblastine sulfate salt. Also, cardiac glycosides, previously identified as hits inhibiting KLK expression in a recent HTS study with breast cancer cells, and reported to have antiproliferative and apoptotic effects also in PC-3, LNCaP, and DU145 cells (30,31), were identified among antiproliferative compounds in our screen, supporting the overall functionality of our assay. Only a few cancer cell selective growth inhibitory compounds were identified in the HTS experiment.…”
Section: Discussionsupporting
confidence: 83%
“…The other HTS hit compounds already in ongoing clinical trials 5 in prostate cancer included doxorubicin, Taxol/paclitaxel, mitoxantrone, suramin, camptothecin, staurosporine, ixabepilone, 17-AAG, epothilone B, MS-275, and vinblastine sulfate salt. Also, cardiac glycosides, previously identified as hits inhibiting KLK expression in a recent HTS study with breast cancer cells, and reported to have antiproliferative and apoptotic effects also in PC-3, LNCaP, and DU145 cells (30,31), were identified among antiproliferative compounds in our screen, supporting the overall functionality of our assay. Only a few cancer cell selective growth inhibitory compounds were identified in the HTS experiment.…”
Section: Discussionsupporting
confidence: 83%
“…These drugs are relevant for cancer treatment since epidemiologic studies have shown that patients treated with cardiac glycosides for heart failure exhibit a reduced cancer rate and less aggressive cancers (11,33,34). Moreover, in vitro studies have previously shown selective cancer killing for some of these cardiac glycosides which we now relate to Ca 2+ signaling and TSGs reactivation (35). Our data suggest that their chemopreventive or chemotherapeutic activity may be in part due to their ability to target Ca 2+ fluxes and reactivate epigenetically silenced TSGs.…”
Section: Discussionmentioning
confidence: 77%
“…However, it is worth noting that there has been no mechanistic explanation reported for efficacy of cardenolide glycosides in retinoblastoma, and these compounds are common hits in cellular screens, particularly as cancer therapies. [129132] Digoxin and ouabain may simply be promiscuous compounds, [133] and considerably less attractive than therapeutic candidates which kill selectively based on mechanisms specific to retinoblastoma.…”
Section: Pre-clinical Progress In Retinoblastoma Therapeuticsmentioning
confidence: 99%